Development and technology study of combination tablet formulations - Atartsetseg, Maralgoo; Lkhavga, Maral; Borbaatar, Battulga; Davjid, Batdorj; Gantur, Ganchimeg; Boldsaikhan, Munkhzaya; Batchuluun, Bujinlkham; Enkhsaikhan, Khuslen; Ryenchindorj, Lkhaasuren; Luvsan, Khurelbaatar; et al. (Journal of Eastern - Western Pharmacology and Pharmacy, 2025)
Seasonal transitions weaken the human immune system, increasing susceptibility to influenza and influenza-like illnesses. These illnesses are caused by viruses that damage the epithelial cells of the respiratory tract, resulting in symptoms such as fever, sore throat, cough, nasal congestion, rhinorrhea, and headache. Severe cases can lead to complications, including pneumonia, acute bronchitis, otitis media, and sinusitis. Combination drugs containing ibuprofen, phenylephrine hydrochloride, and chlorpheniramine maleate effectively manage these conditions. However, tablet formulations with this combination are not yet available in our country. Consequently, we aimed to develop a manufacturing protocol for such a formulation in a domestic pharmaceutical facility and assess its quality. The wet granulation method prepared tablets contain ing the aforementioned combination. Several formula tions were developed and evaluated based on quality parameters specified in the Mongolian Pharmacopoe ia-National Formulary (MP-NF). The Hausner ratio and Carr’s index for formulations A1 (1.13 and 15, respectively), A3 (1.14 and 14.2), and A5 (1.15 and 15.7) indicated “good” flow properties and high compressibility, enabling successful tableting. Formulations A2 and A4 exhibited Hausner ratios of 1.23 and 1.18 and Carr’s indices of 23.5 and 18.9, respectively, reflecting “fair” flow properties and poor compressibility. Tablets could not be compressed from formulation A2 due to granule fragmentation. The successfully compressed formulations (A1, A3, A4, and A5) met all quality criteria stipulated in the Mongolian Pharmacopoeia-National Formulary (MP NF), including appearance, average weight, weight variation, hardness, and disintegration time. A2 was unsuitable for compression among the five formulations due to granule breakage. The remaining formulations (A1, A3, A4, and A5) demonstrated acceptable compression properties, with formulations A1 and A3 showing the shortest disintegration times (3 and 4 minutes, respectively). These findings suggest that formulations A1 and A3 are the most promising candidates for further development.